2007
DOI: 10.5511/plantbiotechnology.24.361
|View full text |Cite
|
Sign up to set email alerts
|

Generation of intracellular reactive oxygen species during the isolation of Brassica napus leaf protoplasts

Abstract: The isolation of leaf protoplasts is a stress-inducing procedure that generates reactive oxygen species (ROS). We found that a cellulase-pectinase enzyme solution used for isolating protoplasts contained peroxidase (POX), catalase (CAT), and superoxide dismutase (SOD) activity, and effectively scavenged externally added hydrogen peroxides. During the isolation of Brassica napus leaf protoplasts, the protoplasts accumulated 1.5 times more intracellular H 2 O 2 than normal leaf cells, but the H 2 O 2 released in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Abundant calcium oxalate crystals accumulated in the ruptured protoplasts, which could puncture other protoplasts ( Pindel, 2007 ; Lin et al, 2018b ), and were observed in the protoplast solution ( Supplementary Figure 1 ). Peroxides released by the ruptured protoplasts could also damage the protoplasts ( de Marco and Roubelakis-Angelakis, 1996 ; Yasuda et al, 2007 ). To address these problems and protect protoplasts from rupturing, a suitable concentration of the reducing agent 2-mercaptoethanol was added to the enzyme solution.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant calcium oxalate crystals accumulated in the ruptured protoplasts, which could puncture other protoplasts ( Pindel, 2007 ; Lin et al, 2018b ), and were observed in the protoplast solution ( Supplementary Figure 1 ). Peroxides released by the ruptured protoplasts could also damage the protoplasts ( de Marco and Roubelakis-Angelakis, 1996 ; Yasuda et al, 2007 ). To address these problems and protect protoplasts from rupturing, a suitable concentration of the reducing agent 2-mercaptoethanol was added to the enzyme solution.…”
Section: Discussionmentioning
confidence: 99%
“…In non-regenerating protoplasts, with a lower capacity of antioxidant machinery, intracellular ROS induced by the stress of isolation can accumulate in a compartment-specific manner (De Marco and RoubelakisAngelakis 1996). Accumulated ROS are associated with increased levels of lipid peroxidation (Papadakis et al 2001) and participate in the initiation of apoptosis-like cell death of cultured protoplasts (Yasuda and Watanabe 2007). In a similar way to protoplast regeneration, the capacity of callus regeneration might be under the control of ROS production systems induced by growth regulators and controlled by antioxidant cellular systems, as previously demonstrated in wheat (Szechynska-Hebda et al 2007).…”
Section: Introductionmentioning
confidence: 90%
“…The isolation procedure can also induce further chromatin condensation and the apoptotic pathway [72]. This condensation is accompanied by a reduction in the scavenging capacity of reactive oxygen species (ROS) [73], which leads to an increased ROS accumulation [74,75]. Recently, the presence of chromatin condensation has also been demonstrated during protoplast isolation followed by subsequent cultivation in a buffer without PGRs [76].…”
Section: The Protoplast Isolation Step As the Key For Reprogrammingmentioning
confidence: 99%